House of Risk Approach in Determining Delay Risk Factors - Kardiani, Rani; Kurniyaningrum, Endah; Yuwono, Bambang Endro; Widiarso, Tulus (Pandawan Sejahtera Indonesia, 2025)
Delays in project completion can lead to significant financial losses, reduced contractor performance, and decreased operational efficiency. This study analyzes the delay factors in the Proton Beam Building construction project at RSPAD Gatot Soebroto, identifying the primary causes and proposing targeted mitigation strategies. A mixed-method approach, combining qualitative interviews and quantitative surveys with key project stakeholders including planning consultants, construction management teams, contractors, and other involved parties is employed. The analysis utilizes the House of Risk (HOR) method to identify and prioritize delay agents and the House of Delay (HOD) method, supplemented by Forum Group Discussions for comprehensive insights. Keyresearch variables encompass human resources, materials, equipment, contract administration, project planning, field conditions, and stakeholder involvement. The study reveals that the primary causes of delays are inadequate planning, design changes, and a shortage of qualified human resources in construction management and planning consulting. The HOR methodology identifies the top three delay agents: Planning not in accordance with regulations (A8), Design changes (A6), and Lack of human resources (A4). To address these issues, the study proposes mitigation strategies, including the creation of a comprehensive checklist for regulatory compliance during planning, ensuring design alignment with applicable regulations, and developing contingency plans to addresspotential human resource shortages. These strategies aim to reduce the most significant delay risks, improve project efficiency, and enhance overall project compliance.